Domestic Tourists' Perceptions of Kelan Beach Attributes, Badung - Bali - Ni Kadek Widya Wijayaningtyas; Luh Nyoman Tri Lilasari; Anom Hery Suasapha (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
This study aims to evaluate domestic tourists' perceptions of the quality of Kelan Beach attributes and to group these attributes. The data analysis methods used are descriptive statistical analysis and exploratory factor analysis. The type of data used is quantitative data with a non-probability sampling technique of 100 respondents. The results show that the attributes "Scenery/Natural Attractions" and "Climate" get the highest average scores, while "Medical Facilities" gets the lowest average score. With factor analysis, 38 statements can be simplified into eight dominant factors, namely "Attractive beach with good facilities" with the highest level of importance, to "Beach with adequate accommodation" with the lowest level of importance. This study recommends improving Kelan Beach facilities and marketing activities to attract more tourists.